Voicing the Imprisonment in Skin: A Critical Study of Hamid's The Last White Man - Ahmad, Shumaila; Rasool , Shamshad; Noor, Anzala (Pakistan Languages and Humanities Review, 2025)
This study explores the racial transformation and emergence of white rage in Mohsin Hamid's novel The Last White Man. It focuses on examining how the loss of whiteness affects the characters' social status and interpersonal relationships. It employs Textual Analysis as a primary method, with Critical Race Theory and Du Bois' sociohistorical concept of race serving as the methodological frameworks. The findings reveal that the transformation of the characters from white to brown triggers white rage that leads to social alienation, identity loss, and emotional neglect. This transformation engenders a profound existential as the characters are striped of the privileges they one enjoyed. A persistent sense of loss haunts them; some respond with suicide attempts while other fall victims to racially motivated violence. The study underscores the urgent need to confront racism by fostering a more equitable and cohesive society primarily through education and literature as exemplified in Hamid’s The Last White Man.